The disclosure of information about organization social responsibility in financial statements: benefits and opportunities - Budrionytė, Ramunė (Buhalterinės apskaitos teorija ir praktika, 2014)
One of this time distinguishing features - business and government organizations assume a greater social responsibility. Businesses and public organizations leaders have identified, that an understanding of social responsibility and social activity opens up a favourable business prospects, increase competitive advantage and, ultimately, ensures greater prestige and profits for the company. However, up to now, the concept of social responsibility is not an unambiguous assessment - this is determined by the different treatment in organizations goals. The social responsibility measures provide multiple benefits for the organization, i.e. a more efficient use of resources, innovative abilities, a better public image, an increased motivation of employees and hence productivity, fewer disputes and strikes, easier to attract the best professionals in lower costs of the search, a lower turnover of employees, a higher acceptance of consumers. All this increases the competitive advantage of organization in the market. In order to gain a competitive advantage for social responsibility initiatives, management of organization should provide the appropriate information about the company’s activities in the field of social responsibility. The information could be provided not only in the public space (such as company web page), but also in the company‘s explanatory notes and (or) in the annual notification. In order to avoid the information chaos, it should be structured according to the following social responsibility assessment areas: 1) environment, 2) human resources, 3) social activities, 4) product development.